MASS-CULTURE: DALAM DIALEKTIKA DENGAN MUSIK KITA - Cecep Kusnendi (Paraguna, 2017)
The  development of music in Indonesia today  are quite  encouraging quantity,  but the quality  is  very doubtful.  The phenomenon is predicted as a result  of the spread of mass-culture which  have  an impact on the proliferation of kitsch  in our music.In our music kitsch  showed  in  repetitive forms,  sensational,  sensual,  sentimentality, vulgar,  glamour,  eroticism,  sex,  etc.  These forms  mainly  seen in the lyrics,  singer's body   movements,  stage   costumes,  and   so  many   repetitions  songs   sold  in  the market.  The  conditions   in  the  realms   of our  music,  is  motivated  by  a  variety problems such  as  economics  which  resulted the  artist (composers)  should  follow the  mass-culture  tasted.  The  other  sad  phenomenon  also  seen   in  the  lack  of infrastructure for the art trainings,  also in adequate number of music critics.   Now, the growth  and  development of the diatonic  and pentatonic's music in our country, showed "kitsch" or product of the mass-culture.